2013
DOI: 10.1534/genetics.113.156075
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Custom Genomic Modifications in Caenorhabditis elegans via a CRISPR–Cas9 System

Abstract: We adapted the CRISPR-Cas9 system for template-mediated repair of targeted double-strand breaks via homologous recombination in Caenorhabditis elegans, enabling customized and efficient genome editing. This system can be used to create specific insertions, deletions, and base pair changes in the germline of C. elegans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
122
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 31 publications
1
122
0
Order By: Relevance
“…Our efforts at Cas9-directed editing succeeded with all 39 GG guides. In contrast, success was infrequent and unpredictable with guides lacking a 39 GG in our study and in published studies (Table S1) (Chiu et al 2013;Cho et al 2013;Dickinson et al 2013;Friedland et al 2013;Katic and Grosshans 2013;Lo et al 2013;Tzur et al 2013;Liu et al 2014;Paix et al 2014;Shen et al 2014;Waaijers and Boxem 2014;Zhao et al 2014). We also found that a 39 GG dinucleotide reliably increased the frequency of genome editing at all targets, even related targets for which the 39 GG-shift guides supported a low to modest frequency of editing.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Our efforts at Cas9-directed editing succeeded with all 39 GG guides. In contrast, success was infrequent and unpredictable with guides lacking a 39 GG in our study and in published studies (Table S1) (Chiu et al 2013;Cho et al 2013;Dickinson et al 2013;Friedland et al 2013;Katic and Grosshans 2013;Lo et al 2013;Tzur et al 2013;Liu et al 2014;Paix et al 2014;Shen et al 2014;Waaijers and Boxem 2014;Zhao et al 2014). We also found that a 39 GG dinucleotide reliably increased the frequency of genome editing at all targets, even related targets for which the 39 GG-shift guides supported a low to modest frequency of editing.…”
supporting
confidence: 56%
“…The initial report describing the successful use of Cas9 in C. elegans demonstrated a range of editing frequencies from 0.5 to 80%, with only two targets exceeding 4% . Subsequent publications also reported variably low mutagenesis rates that required molecular screening of hundreds of animals or required the desired mutation to cause an easily detectable mutant phenotype or to be introduced in tandem with a coselection marker (Chiu et al 2013;Cho et al 2013;Dickinson et al 2013;Katic and Grosshans 2013;Lo et al 2013;Tzur et al 2013;Waaijers et al 2013;Chen et al 2014;Liu et al 2014;Paix et al 2014;Shen et al 2014;Zhao et al 2014). More recent studies greatly improved the odds of detecting a targeted mutation through the simultaneous co-conversion of a mutation in an unrelated target that causes a visible phenotype (Arribere et al 2014;Kim et al 2014;Ward 2014).…”
mentioning
confidence: 99%
“…To induce mutations likely to be molecular nulls, we utilized CRISPR-associated protein 9 (Cas9) technology Tzur et al 2013). We created the single guide RNA (sgRNA) plasmid pCL45 by replacing the unc-119 targeting site in the plasmid PU6::unc-119_sgRNA (Addgene) with a target site near the start of exon 4 on the opposite strand (59-ggaagaaaaatacgccaaggAGG-39).…”
Section: Crispr/cas9 Induced Mutation Of Spe-47mentioning
confidence: 99%
“…Because we could not assess the severity of the spe-47(hc198) mutation on overall protein function, we created insertion/ deletion mutations (indels) in spe-47 using CRISPR/Cas9 technology Tzur et al 2013). CRISPR/Cas9 employs both the Cas9 nuclease from Streptococcus pyogenes and a sgRNA containing a targeting sequence directed to the desired site in the genome.…”
Section: Spe-47(hc198) Is a Semidominant Mutation Compared To Crispr/mentioning
confidence: 99%
“…Techniques to precisely manipulate genomes exist for many model organisms (Storici et al 2003;Gratz et al 2013;Hwang et al 2013;Jiang et al 2013;Tzur et al 2013), but not all features of these approaches are easily portable to closely related species. The genus Saccharomyces is highly experimentally tractable, and laboratory strains of all seven natural species can be genetically manipulated Liti et al 2013).…”
mentioning
confidence: 99%